Усан дахь нягтын флуктуацаас үүсэх гэрлийн сарнил - Ш, Мөнхжаргал; Ч, Баярхүү (Scientific transaction of the National University of Mongolia. Physics, 2022)
In a molecular level of water structure, clusters exist in a combination of continuous composition and decomposition. Purpose of this work is to find out how these structures can be connected with the Mongolian and the Earst medicine understanding. Has been done number of works on this subject and resently used cluster structure model in order to investigate the phase structures in water.